2007
DOI: 10.1111/j.1365-2982.2007.00949.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal gastric suctioning results in chronic visceral and somatic hyperalgesia: role of corticotropin releasing factor

Abstract: Gastric suctioning is common in neonatal intensive care units. Studies suggest that gastric suctioning in premature infants may play a role in the development of visceral hyperalgesia. We hypothesized that repeated orogastric suctioning during the neonatal period results in chronic alterations in visceral and somatic sensation through a corticotropin-releasing factor mediated mechanism. Neonatal male Long Evans rats (n = 13) received daily orogastric suctioning for 10 days starting at postnatal day two (P2). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 46 publications
3
38
0
Order By: Relevance
“…The adult pain hypersensitivity can be blocked by preemptive administration of glutamate receptor antagonists (given at the time of pain induction) in the case of acid injection, 38 or corticotrophin releasing factor 1 antagonist in case of nasogastric suctioning. 39 These findings and many others indicate that the changes in visceral pain responses induced during infancy can be modified by changing the neurochemical milieu during the painful experience.…”
Section: Visceral Pain During Development Alter Pain Responses In Adumentioning
confidence: 86%
“…The adult pain hypersensitivity can be blocked by preemptive administration of glutamate receptor antagonists (given at the time of pain induction) in the case of acid injection, 38 or corticotrophin releasing factor 1 antagonist in case of nasogastric suctioning. 39 These findings and many others indicate that the changes in visceral pain responses induced during infancy can be modified by changing the neurochemical milieu during the painful experience.…”
Section: Visceral Pain During Development Alter Pain Responses In Adumentioning
confidence: 86%
“…88,90 Studies on NCI rodents also reported an increase in TRPA1 100 or its family member TRP vanilloid 1 (TRPV1) 101 expression in colon-specific dorsal root ganglion neurons and an increase in the number of CRD-responsive dorsal horn neurons. 103 Neonatal irritation of other organs, including the bladder 104 and stomach, 105 has also been shown to increase colorectal sensitivity in adult mice, suggesting that the colon may be exquisitely sensitive to neonatal perturbations, which may contribute to the greater prevalence of IBS among the general population, in comparison to other related chronic pelvic pain disorders.…”
Section: Irritable Bowel Syndromementioning
confidence: 97%
“…Physical abuse may lead to abdominal injury, which has been associated with increased risk of unexplained gastrointestinal symptoms, 46,47 possibly through long-lasting changes in nociception. Ringel and colleagues observed increased pain to gut distention and associated changes in central pain processing in adult patients with unexplained abdominal pain who have been abused compared with those who have not.…”
Section: G a S T Roin T Es T Ina L Sy Mp To Ms A Nd Chil D M A Lt R Ementioning
confidence: 99%